Participants' and implementors' views on the adaptation of the Parenting for Lifelong Health Teen Programme to address both violence against children and violence against women - Davidson, Natalie (Department of Psychology, 2023)
This study collected views about how the Parenting for Lifelong Health (PLH) Teen programme might be adapted to include a more explicit focus on preventing VAW (in addition to its current strength in preventing VAC) and engagement of fathers for the Zimbabwean context. Violence against women (VAW) and violence against children (VAC) intersect in various and damaging ways. Parenting programmes have been identified as a potentially successful way to deal with both simultaneously, given the effect of violence in the family on parenting and the importance of parenting as a key point of intervention to prevent present and future violence. Participants were caregiver and teen (10-17 years) participants of the PLH Teen programme and fathers, mothers and teens (10-17 years) who were not PLH participants; as well as PLH facilitators, from the Mazowe district, Zimbabwe. Qualitative data were collected via Zoom for the individual interviews with the facilitators of the PLH programme and WhatsApp for focus group discussions for the rest of the participants, given the current global pandemic. The findings of this study and a review of relevant literature suggest that a gender-transformative approach, the inclusion of a community focus and the active recruitment and engagement of fathers is needed in terms of the process for the adapted programme. In terms of the content for the adapted programme, the study's findings suggest that there is a need to strengthen and expand the existing communication and conflict resolution skills to consider the couple and the parent-teen relationships and interactions. They also suggest that the budgeting and saving component in the current PLH Teen Programme could perhaps include business skills. Lastly, this study suggests that there is potential for the future use of virtual data collection in low- and middle income countries where there is limited access to video conferencing. This study contributes both to the important work preventing VAW and VAC in one programme as well as the future use of messaging services such as WhatsApp as a data collection tool.